Interview: Interview with Lisa Shipley. (August 2013) - Shipley, Lisa
Lisa Shipley is Vice President of Pharmacokinetics, Pharmacodynamics and Drug Metabolism at Merck Research Laboratories. She is responsible for preclinical and clinical ADME activities and molecular biomarker assay development activities at all Merck research sites and support of all programs from discovery through to post-product launch. Prior to joining Merck in 2008, Shipley spent over 20 years at Eli Lilly and Company in roles of increasing responsibility, including the positions of executive director at Lean Six Sigma and vice president of Drug Disposition, PK/PD and Trial Simulations. Shipley obtained her undergraduate degree from McDaniel College and her doctoral degree in Pharmacology and Toxicology from the University of Maryland at Baltimore. This interview was conducted by Lisa Parks, Assistant Commissioning Editor of Bioanalysis .